1992
DOI: 10.1002/ptr.2650060604
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of Ganoderma lucidum, an edible mushroom, on intraperitoneally implanted lewis lung carcinoma in synergenic mice

Abstract: The antitumour activity of Ganoderma lucidurn, called 'Ling-Zhi or holy mushroom' in Chinese traditional medicine, was investigated on intraperitoneally implanted Lewis lung carcinoma in syngeneic C57BL/6 mice. An aqueous extract of Ling-Zhi significantly increased the life span of tumour-implanted mice, when administered intraperitoneally alone or in combination with cytotoxic antitumour drugs (Adriamycin, fluorouracil, thioguanine, methotrexate, Cisplatin) or a synthetic immunomodulator (Imexon). The aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 10 publications
0
45
0
1
Order By: Relevance
“…3) Previous studies of G. lucidum have mainly concentrated on the medicinal properties of this mushroom. Limited information is available on the activities of the enzymes which modify oligo-and polysaccharides present in the mushroom, though preliminary reports [4][5][6][7] have shown that G. lucidum used galactose as the best carbon source for producing potentialized ganoderan having anti-tumor and anti-complementary activity. We found that cultivated G. lucidum produced a wide variety of glycosidases, and had strong a-galactosidase activity.…”
mentioning
confidence: 99%
“…3) Previous studies of G. lucidum have mainly concentrated on the medicinal properties of this mushroom. Limited information is available on the activities of the enzymes which modify oligo-and polysaccharides present in the mushroom, though preliminary reports [4][5][6][7] have shown that G. lucidum used galactose as the best carbon source for producing potentialized ganoderan having anti-tumor and anti-complementary activity. We found that cultivated G. lucidum produced a wide variety of glycosidases, and had strong a-galactosidase activity.…”
mentioning
confidence: 99%
“…Its medical effects on cancer, hypertension, hepatitis, and hypercholesterolemia have been demonstrated by pharmacological studies in the past two decades. [1][2][3][4] This fungus has attracted considerable attention partly because the polysaccharides isolated from the fruit bodies and the mycelium have shown antitumor and hyperglycemic activity. 3,5,6) However, the active components in the spores of G. lucidum have rarely been studied owing to the difficulty in collection and sporoderm-breaking of the spores.…”
mentioning
confidence: 99%
“…Similar to the results obtained using the mouse sarcoma 180 cell model, a polysaccharide extract of Ganoderma lucidum has also been shown to inhibit the growth of Lewis lung carcinoma cells in mice (19,21). The sulfate derivatives of D-glucans demonstrate a significantly higher antitumor activity against Ehrlich ascites carcinoma (22).…”
Section: Discussionmentioning
confidence: 63%